The Effect of Corporate Social Responsibility on Tax Avoidance: The Moderating Role of Earnings Management - Heni Yusnita (The Institute of Academic Research and Publication (IARP), 2023)
This research was conducted to analyze and prove the partial effect of corporate social responsibility on tax avoidance and to analyze and prove the effect of earnings management variables in moderating corporate social responsibility on tax avoidance. The research design is a multiple linear regression analysis and Moderated Regression Analysis (MRA) using the SPSS version 25 program. The subjects are the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI). 19 companies meet the criteria to be used as a sample. The results show that: corporate social responsibility has no significant effect on tax avoidance. Meanwhile, Earnings Management significantly strengthens the moderate effect of corporate social responsibility on tax avoidance.